ISU ISLAMISASI ILMU PENGETAHUAN DALAM PEMIKIRAN MUHAMMAD MUMTAZ ALI - Heru Saiful Anwar; Safiruddin Al Baqi (MA'ALIM: Jurnal Pendidikan Islam, 2020)
Muslim scholars or scientists are currently faced with a dilemma of thought and actions in responding to the challenges of the globalization. On the one hand, the onslaught of western thought such as secularism and liberalism is very strong, while on the other hand they must maintain the principles of Islamic law. So that their actions do not come out of Islamic law, it is very important for Muslim scientists to understand the concept of Islamization of Science. The figure who initiated this thought was Prof. Syed Muhammad Naquib al-Attas who then continues until now, one of them is Muhammad Mumtaz Ali. Muhammad Mumtaz Ali's works related to the Islamization of Science emphasize the importance of prioritizing the Islamization of science for Muslim scientists. The spirit of Islamization must continue to be strengthened for the advancement of Muslims. The vision and mission of the Islamization of Science will be difficult to achieve if Muslims are not united to achieve it. All Muslim scientists in various fields of knowledge are expected to understand Islamic law well, so that the knowledge they spread will not conflict with the rules of Allah SWT.